Personality Disorder, Institutional Violence and Self-Esteem in three Forensic Intellectual Disability Samples - van Logten, Anne (Student Undergraduate Research E-journal!, 2015)
The relationship between personality disorder and institutional violence and the mediating effect of self-esteem are investigated among offenders in specialist forensic services for individuals with intellectual disability. Additionally, attention has been paid to the predictive ability of two diagnostic approaches in this respect. The results of the analyses are distinguished across three levels of security. Differing results has been found for those various samples. This study makes clear that it is important to focus on strengthening self-esteem in intervention programs in high secure settings to reduce the prevalence of institutional violence in individuals with intellectual disability with comorbid personality disorder.